The biosynthesis of EGCG, theanine and caffeine in response to temperature is mediated by hormone signal transduction factors in tea plant (Camellia sinensis L.) - Zhu, Qiufang; Liu, Lijia; Lu, Xiaofeng; Du, Xinxin; Xiang, Ping; Cheng, Bosi; Tan, Meng; Huang, Jiaxin; Wu, Lijiao; Kong, Weilong; Shi, Yutao; Wu, Liangyu; et al. (Frontiers in Plant Science, 2023)
As the main flavor components of tea, the contents of epigallocatechin-3-gallate (EGCG), theanine and caffeine are regulated by ambient temperature. However, whether the biosynthesis of EGCG, theanine and caffeine in response to temperature is regulated by endogenous hormones and its mechanism is still unclear. In this study, we investigated the internal intricate relationships between the biosynthesis of these three main taste components, endogenous hormones, and structural genes in tea plants at different temperatures treatments. The results showed that indoleacetic acid (IAA), gibberellin 1(GA1) and gibberellin 3(GA3) were significantly correlated with the content of EGCG; Jasmonic acid (JA), jasmonate-isoleucine (JA-Ile) and methyl jasmonate (MeJA) were strongly correlated with theanine content; IAA, GA1 and gibberellin 4(GA4) were significantly correlated with caffeine content at different temperatures. According to the results of multi-omics analysis, we speculate the regulatory mechanisms: IAA, GA1 and GA3 up-regulated the expressions of chalcone synthase (CsCHS) and trans-cinnamate 4-monooxygenase (CsC4H) mediated by the signal transduction factors auxin-responsive protein IAA (CsIAA) and DELLA protein (CsDELLA), respectively, which promoted the biosynthesis of EGCG; IAA, GA3 and GA1 up-regulated the expression of CsCHS and anthocyanidin synthase (CsANS) mediated by CsIAA and CsDELLA, respectively, via transcription factors WRKY DNA-binding protein (CsWRKY) , and promoted the biosynthesis of EGCG; JA, JA-Ile and MeJA jointly up-regulated the expression of carbonic anhydrase (CsCA) and down-regulated the expression of glutamate decarboxylase (CsgadB) mediated by the signal transduction factors glutamate decarboxylase (CsJAZ), and promoted the biosynthesis of theanine; JA, JA-Ile and MeJA also jointly inhibited the expression of CsgadB mediated by CsJAZ via transcription factors CsWRKY and AP2 family protein (CsAP2), which promoted the biosynthesis of theanine; IAA inhibited the expression of adenylosuccinate synthase (CspurA) mediated by CsIAA via transcription factors CsWRKY; GA1 and gibberellin 4 (GA4) inhibited the expression of CspurA mediated by CsDELLA through transcription factors CsWRKY, which promoted the biosynthesis of caffeine. These findings revealed that the underlying mechanism of biosynthesis of the main taste components in tea plant in response to temperature was mediated by hormone signal transduction factors, thereby providing novel insights into improving the quality of tea.